Trends Of Polish Enterprises In Risk Management - Puto, Agnieszka; Koscielniak, Helena; Bajdor, Paula; Budzik-Nowodzinska, Iwetta (European Scientific Journal, ESJ, 2016)
The beginnings of the implementation of the concept of risk management in the functioning of enterprises stretches back to the middle of the 20th century. Initially they first and foremost signified insurance protection. Subsequent to this, companies began to perceive that not all risk may be insured against and consequently implemented appropriate actions by controlling the level of risk and its impact on enterprises. At the end of the last century, the idea of a complex risk management developed, thus encompassing all types of threats existing in an enterprise (Wieterska 2011, p.11). The effect of the development of the concept of risk management is the formation of a multitude of scientific concepts relating to risk and the international standards of risk management in organizations. The problems associated with the implementation of the systems of risk management have become the subject matter of multiple research projects and works. In the herein paper, the authors at hand present the idea of risk management in Polish enterprises.